Determinants of Mobile Banking Adoption in Kathmandu Valley - Shrestha, Sahil (Nepalese Journal of Finance, 2025)
This study examines the determinants of mobile banking adoption in Kathmandu Valley. Adoption of mobile banking is the dependent variable. The selected independent variables are perceived usefulness, perceived ease of use, trustworthiness, accessibility and social influence. The primary sources of data is used to assess the opinions of respondents regarding perceived usefulness, perceived ease of use, trustworthiness, accessibility, social influence and adoption of mobile banking. The study is based on the primary data of 126 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and determinants of mobile banking adoption in Kathmandu Valley. The study showed a positive impact of perceived usefulness on adoption of mobile banking. It indicates that perceived usefulness leads to increase the adoption of mobile banking. Likewise, the study showed a positive impact of perceived ease of use on adoption of mobile banking. It indicates that perceived ease of use leads to increase the adoption of mobile banking. Similarly, the study showed a positive impact of trustworthiness on adoption of mobile banking. It indicates that secure online transactions through mobile banking leads to increase the adoption of mobile banking. Further, the study showed a positive impact of accessibility on adoption of mobile banking. It indicates that more access of the app leads to increase the adoption of mobile banking. Moreover, the study showed a positive impact of social influence on adoption of mobile banking. It indicates that social awareness regarding digital banking leads to increase the adoption of mobile banking.